Virilization by an Ovarian Tumor: Presentation Is Not Always Acute - Amanda Tjitro BS; Debra A. Wong MD; Adnan Ajmal MD; Kajal Buddhdev MD; Robert Brady MD (SAGE Publishing, 2022)
Androgen-producing steroid cell ovarian tumors are rare, comprising less than 1% of ovarian neoplasms, and can present with infertility and rapid virilization. Here we discuss the case of a 28-year-old woman who presented with an unusually insidious 2-year history of infertility, hirsutism, and clitoromegaly who was found to have an elevated serum testosterone and a left ovarian mass. She underwent oophorectomy and pathology revealed a steroid cell tumor, not otherwise specified (NOS), with no malignant features. Following surgery, the patient's hyperandrogenic symptoms resolved with normalization of testosterone within 6 months, and she was able to conceive spontaneously. In reproductive-aged women with progressive hyperandrogenic symptoms, androgen-producing tumors, including those of ovarian origin, should be suspected. Thorough investigation, including plasma hormone levels and tumor histology, can lead to accurate diagnosis and management. Treatment should be guided by histology and surgical staging, with consideration for future fertility desires. Women who have not completed childbearing can undergo unilateral oophorectomy or tumor resection for benign tumors, with close monitoring of sex hormone levels postoperatively.